Mensuração da eficiência dos terminais brasileiros movimentadores de granéis após a implementação da lei n° 12.815/2013 via análise envoltória de dados - Cipriano, Paula (2019)
Due to the continued growth of international trade flows and the importance of the activity for Brazil's economic growth, and more recently, with the promulgation of the new ports law, Law no. 12.815, of June 5th 2013, that aims to modernization of port management and improvement of the governance model of Brazilian ports, a better understanding of efficiency measurement tools is fundamental. The use of Data Envelopment Analysis (DEA) to measure port efficiency has been widely used because it is a non-parametric mathematical model that uses multiple input and output data, in which it is expected to make a significant contribution to the basis of planning opportunities and best practices. With the objective of measuring and evaluating the efficiency gains of port terminals for bulk cargo handling before and after Law No. 12,815, this research analyzed a set of 25 bulks carrier port terminals from 2013 to 2018, in total of 150 decision making units (DMU). In line with the data provided by the ANTAQ’s (National Waterway Transportation Agency) annual report the input considered was number of berth and the outputs were the number of vessels received and the total cargo load, in order to measure and evaluate operational efficiency of bulk terminals in Brazil. Regarding the application of the DEA and the identification of port efficiency, and especially in the role of a strong management support tool, the results obtained reinforce that Law n° 12.815/2013 contributed to the growth of the port sector, reaching the objective proposed by the study.